Internet-based acceptance and commitment therapy (I-ACT) for elite ice hockey players: a quasi-experimental multiple-cohort intervention study - Reinebo, G.; Jansson-Fröjmark, M.; Parling, T.; Andersson, G.; Lindner, P.; Lundgren, T. (International Journal of Sport and Exercise Psychology, 2025)
Internet-based interventions have yielded promising results in clinical psychology but remain unexplored in sports. The current study investigated internet-based acceptance and commitment therapy (I-ACT) in elite ice hockey players to enhance performance and promote psychologically sustainable sports participation. Fifty-five ice hockey players from three national-level leagues in Sweden took part in a 7-week intervention. There were two consecutive starts of I-ACT during the season (I-ACT1, N = 44; I-ACT2, N = 11), and the outfield players were compared to players in the rest of the leagues (N = 1051) on objective performances (goals, assists, Total points, PlusMinus statistics). Psychological flexibility, subjective performance, and mental health-related outcomes were also investigated among I-ACT players. Linear mixed models were used to analyse objective and subjective outcomes, except for save percentage in goaltenders which was analysed using a within-group repeated measures ANOVA. Statistically significant effects were found on PlusMinus statistics in I-ACT2 compared to other league players from pre- to post-intervention (B = 0.177, SE = 0.061, 95% CI = 0.057-0.294, p = .004, d = 0.69), which was maintained at follow-up. No significant effects were found on objective performance in I-ACT1 nor in goaltenders. Significant within-group effects were found on increased psychological flexibility and sleep quality in I-ACT players. No effects were found on subjective performance ratings, quality of life, or general anxiety. 5.45% reported negative experiences from the intervention. Internet-based interventions can serve as a promising alternative to make psychological interventions more accessible in sports but need further investigation.